ANALISIS PERSEPSI KUALITAS, KEPUASAN PELANGGAN DAN REPUTASI PERUSAHAAN TERHADAP MINAT ULANG MENGGUNAKAN JASA TRANSPORTASI - Wolok, Tineke (Magister Manajemen Universitas Wisnuwardhana, 2018)
The concept of customer satisfaction is important for marketing managers where customer satisfaction can encourage repeat purchases. Consumer satisfaction is an important asset for the company because it can be used as an indicator of the company's quality and income in the future. The population of this study was 137 passengers a month. Determination of the number of samples in this study using a statistical approach, the sample size in the study amounted to 58 respondents. the results of the analysis and discussion above, the conclusions that can be drawn in this study are as follows: (1) Simultaneous problems between the influence of perceived quality, customer satisfaction and company reputation simultaneously have a significant effect on re-interest in using Gorontalo Tour & Travel transportation services. The partial problem between the influence of perceived quality, customer satisfaction and company reputation has a significant effect on re-interest in using Gorontalo Tour & Travel transportation services. Keywords: Quality Perception, Customer Perception, Company Problems, Retention using Transportation